Tradisi Ma’ulelean sebagai Salah Satu Cara Mentransmisikan Ilmu Pengetahuan Masyarakat Mengkendek - Mandalling Pasangka', Calveny (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2024)
Abstract, This research focuses on the ma’ulelean tradition, an oral tradition of the Mengkendek community, a sub-ethnic group of the Toraja in South Sulawesi, Indonesia. Ulelean is one of the ways the community transmits moral, ethical, and cosmological values to the next generation while strengthening the Mengkendek cultural identity amidst the challenges of modernization. This study aims to understand the definition, function, and values contained within the ma’ulelean tradition, as well as its role in maintaining social bonds. The methodology used is a qualitative literature approach through literature analysis, interviews, and related documents, focusing on the Mengkendek region. The literature review shows that ma’ulelean contains moral teachings that guide the community to live harmoniously with nature and ancestors. However, amid the integration of church teachings, challenges arise when traditional values within the ma’ulelean tradition are perceived as less aligned with Christian values. Some church members view the ma’ulelean tradition as part of animistic beliefs that conflict with monotheism. The research findings reveal that, despite existing tensions, constructive cultural dialogue has the potential to support the preservation of this oral tradition without disregarding religious teachings.